Impact of Arts Education on Holistic Development: A Case Study of Elementary Students at SD Melong Mandiri 4, Cimahi - Komala, Icuh; Wahyudin, Asep; Nugraha, Asep (Nusa Putra University, 2024)
Arts and culture education should be addressed in elementary school curricula, even though it has great potential in developing essential skills for students. This research explores the benefits of arts education for elementary school students at SD Melong Mandiri IV, Cimahi. This research involved three classes of samples using a quasi-experimental design. Data collection methods include observation, interviews, and skills tests, which are analyzed using multivariate analysis. The research results show that arts education significantly develops students' creativity, imagination, and social, cognitive, and fine motor skills. These findings emphasize the importance of integrating arts education in the elementary school curriculum to support students' holistic development. The implications of this research indicate the need for inclusive education policies, comprehensive teacher training, and further research with more rigorous designs to strengthen empirical evidence regarding the benefits of arts education